2007
DOI: 10.1002/ps.1381
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas‐induced defence molecules in rice plants against leaffolder (Cnaphalocrocis medinalis) pest

Abstract: Fluorescent pseudomonad strains Pf1, TDK1 and PY15 individually and in combination were evaluated against leaffolder, Cnaphalocrocis medinalis Guen., in rice under in vitro, glasshouse and field conditions. Among the various treatments used, a combination of Pf1, TDK1 and PY15 strains effectively reduced the incidence of leaffolder pest in rice plants to an extent comparable with chlorpyrifos-methyl. In addition, morphogenesis of the insect pest in all stages, larval, pupal and adult, was greatly affected by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
33
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 41 publications
5
33
0
1
Order By: Relevance
“…However, chemicals are slowly being replaced by naturally-occurring and introduced biocontrol agents (Radjacommare et al 2002;Saravanakumar et al 2007b). Pseudomonas fluorescens has been mainly used to manage soil-borne diseases and limited success has been achieved in the management of virus diseases (Maurhofer et al 1994;Raupach et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…However, chemicals are slowly being replaced by naturally-occurring and introduced biocontrol agents (Radjacommare et al 2002;Saravanakumar et al 2007b). Pseudomonas fluorescens has been mainly used to manage soil-borne diseases and limited success has been achieved in the management of virus diseases (Maurhofer et al 1994;Raupach et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, the Pseudomonas fluorescens and endophytic Bacillus subtilis have received particular attention throughout the global science because of their catabolic versatility, excellent root colonizing ability and their capacity to produce a wide range of enzymes and metabolites that favour the plant withstand under varied biotic and abiotic stress conditions (Ramamoorthy et al 2001;Vivekananthan et al 2004;Mayak et al 2004;Saravanakumar and Samiyappan 2007). Though there are several reports on the management of plant diseases (Wang et al 2000;Saravanakumar et al 2009) and pests (Saravanakumar et al 2007a) using PGPB, very little is known about the role of PGPB in mediating drought resistance in field crops. Therefore, the objective was fixed: (a) to evaluate the promising strains of P. fluorescens and B. subtilis to enhance drought resistance on green gram plants and (b) to study the differential enzymatic and protein activity during water stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The marked strains grew well in King's B medium containing rifampicin (190 mg mL (1 ), actinomycin D (100 mg mL (1 ), penicillin (90 mg mL (1 ) and streptomycin (30 mg mL (1 ). These strains were previously demonstrated to be effective in the suppression of rice leaffolder, Cnaphalocrosis medinalis (Saravanakumar et al 2007) and rice sheath rot disease caused by Sarocladium oryzae (Saravanakumar et al 2009). The bacterial cultures were maintained in King's broth B (KBB) (King, Ward, and Raney 1954) in 30% glycerol at (808C.…”
mentioning
confidence: 97%
“…The results of our in vitro tests confirmed that P. fluorescens strains used possess direct antagonism against M. graminicola juveniles and eggs. The PF1, TDK1 and PY15 strains are reported to produce metabolites such as phenazine, oxychlorophine, diacetyl phloroglusinol (DAPG) and hydrogen cyanid (HCN) (Nandakumar et al 2001;Saravanakumar and Samiyappan 2006). The DAPG and HCN produced by P. fluorescens was shown to have nematicidal activity against potato cyst nematode, Globodera rostochiensis eggs (Cronin et al 1997) and root knot nematode Meloidogyne javanica juveniles Siddiqui, Shaukat, Sheikh, and Khan 2006) and the same might contribute as mechanism of M. graminicola mortality and egg hatching inhibition.…”
mentioning
confidence: 99%
See 1 more Smart Citation